filmov
tv
Prove identity (1+ tanh x)/(1- tanh x) = e^(2x). Hyperbolic functions
Показать описание
Ms Shaws Math Class
Рекомендации по теме
0:04:31
Prove identity (1+ tanh x)/(1- tanh x) = e^(2x). Hyperbolic functions
0:00:07
prove that tanh(x+y)=tanhx+tanhy/1+tanhx tanhy
0:05:34
Hyperbolic Help: Prove: ((1+tanhx)/(1-tanhx))^n=(1+tanh(nx))/(1-tanh(nx) )
0:07:09
tanh(x+y) = (tanh x + tanh y)/(1+ tanh x tanh y) || Hyperbolic Trigonometric Identities
0:24:28
Verifying Hyperbolic Trig Identities
0:06:51
Prove Hyperbolic Identity sech2x=1-tanh2x | Functions and Limits | Hyperbolic | Pythagoras Math
0:04:52
Inverse tanh(x)
0:03:23
Inverse function of tanh x
0:10:12
Hyperbolic Trig Functions - Basic Introduction
0:04:59
Proving the Identity
0:04:22
Derivative of Inverse Hyperbolic Trigonometry: tanh^-1(x)
0:05:37
1 - tanh^2 x = sech^2 x || Hyperbolic Trigonometric Identities
0:16:54
tanhx-tanhy divided by 1 - tanhxtanhy=tanh(x-y)
0:04:41
Prove that tanh^2 (x) = 1—sech^2 (x) | hyperbolic trig identities part 2
0:00:33
Prove the identity. tanh(x+y)=tanhx+tanhy/1+tanhx tanhy
0:08:10
tanh(x-y) = (tanh x - tanh y)/(1- tanh x tanh y) || Hyperbolic Trigonometric Identities
0:00:41
prof that tanh(X+Y) = {tanhX + tanhY}/1+ tanhX.tanhY
0:13:28
Proving Hyperbolic Identities (5 examples)
0:02:54
`(1+tanh(x/2))/(1-tanh(x/2))=`
0:04:54
Show the derivative of fourth root of (1+ tanh)/(1- tanh) = 1/2 e^(x/2). Inverse Hyperbolic Function
0:06:00
1 - tanh^2 x = sech^2 x - How to prove hyperbolic Trigonometric Identity 1 - tanh^2 x = sech^2 x
0:02:00
Hyperbolic Trigonometry Identity Proof: 1-tanh^2(x) = sech^2(x)
0:02:54
Prove the trig identity: 1+tan^2 = sec^2
0:05:53
Hyperbolic Trigonometry Identity Proof: cosh(x+y) = cosh(x)cosh(y) + sinh(x)sinh(y)